2022
DOI: 10.1002/cbin.11977
|View full text |Cite
|
Sign up to set email alerts
|

Study of frequency and inheritance model of ACE1 I/D and ACE2 rs2285666 polymorphisms in COVID‐19 patients with varying severity of lung involvement and its effect on serum cytokines levels

Abstract: The angiotensin‐converting enzyme (ACE) has been shown to play a role as a receptor for the COVID‐19 virus. This virus usually gets into cells and infects them by attaching to their glycoprotein receptors, which are found on the ACE2 receptor. The aim of this study was to evaluate the frequency and inheritance of ACE1 I/D and ACE2 rs2285666 polymorphisms in COVID‐19 patients with varying severity of lung involvement and its effect on serum cytokines levels of interleukin (IL)‐1 and IL‐6 and laboratory paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Interestingly, we observed higher serum IL-6 levels among patients harbouring the CT variant compared to the wild CC type of rs2285666, as provided in the supplementary files ( Table S4 ). However, Beyranvand et al did not find any correlation between IL-6 levels and SNP polymorphisms of the two target receptors [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed higher serum IL-6 levels among patients harbouring the CT variant compared to the wild CC type of rs2285666, as provided in the supplementary files ( Table S4 ). However, Beyranvand et al did not find any correlation between IL-6 levels and SNP polymorphisms of the two target receptors [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the association of rs2285666 (ACE2) and rs12329760 (TMPRSS2) with COVID-19 severity [ 35 , 36 , 43 , 44 , 45 ]. Interestingly, these studies have either confirmed [ 13 , 36 , 46 , 47 , 48 , 49 , 50 , 51 ] or contradicted [ 52 , 53 , 54 , 55 ] the association between rs2285666 and/or rs12329760 with COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%